Metal phthalocyanines as catalyst precursors of metallated carbon nanotubes - Alanís, Antonio; Kharissova, Oxana Vasilievna; Kharisov, Boris I. (Bentham Science Publishers, 2019)
Abstract: Background: The addition of nanoparticles to cellulose paper can improve its mechanical strength, chemical stability, biocompatibility and hydrophobic properties. Silica nanoparticles are known to be inert, hydrophobic, biocompatible, biodegradable and have a good distribution being deposited on surfaces. The main characteristics of 20 nm SiO2 nanoparticles are good chemical and thermal stability with a melting point of 1610-1728°C, a boiling point of 2230°C with a purity of 99.5%. Objective: To carry out the hydrophobization of paper based on Kraft cellulose and on cellulose obtained from soybean husk with 20-nm size SiO2 nanoparticles and to study hydrophobicity, morphology and topography of the prepared composites. Methods: The ground and roasted soybean husk was treated with a NaOH, washed and dried. Hydrophobization of paper was carried in aqueous medium by SiO2 addition in weight ratios “paper-SiO2 ” of 0.01-0.05 wt.%, stirring, filtration and drying. The obtained cellulose sheet composites were characterized by scanning electron microscopy (SEM), transmisión electron microscopy (TEM), FTIRspectroscopy, Mullen proofs of hydrophobicity, and contact angle measurements. Results: The mechanical properties of paper nanocomposites (tensile strength and compression) increased considerably by varying the concentrations. The tensile strength increased by 41-46% and the compressive strength increased by 55-56%. The existence of fiber nanofoils, good adhesion of 20-nm SiO2 nanoparticles to the paper surface, and their homogeneous distribution were observed. Conclusion: Cellulose was successfully obtained from soybean husk, applying the alkaline-based extraction method. A good reinforcement of cellulose fibers is observed due to the outstanding characteristics of the silicon dioxide nanoparticles.